The road to seagrass restoration at scale using engineering - Richard Unsworth (Ecological Engineering, 2025)
Seagrass restoration efforts have been ongoing for decades, with early innovations dating back to the 1970s. While there has been progress, many projects have high failure rates, but the consensus within the literature is that increasing spatial scale will lead to higher success rates. To achieve scaled-up restoration, innovation in the context of mechanised approaches is required that can reduce the costs and labour-intensive processes and improve reliability. This review paper focuses on the restoration of seagrass meadows and how engineering solutions have been used to help scale up these efforts. The paper examines the different stages within seagrass restoration and how mechanised approaches have been used to date, along with their levels of success or failure. Various stages of restoration are examined, from seed collection, separation, storage, planting, and the biological and environmental engineering challenges associated with upscaling these efforts. The review focuses primarily on Zostera species due to its dominance in the literature, but expands to other species where possible. Although extensive mechanised approaches have been used (e.g. seed planting sleds), a common thread through the studies remains the limited underpinning understanding of the biology to improve the use of these methods and a solid understanding of the relative merits of the use of these techniques. Despite innovations, seagrass restoration is still marked by high failure rates. More interdisciplinary work is required to link biological and engineering solutions to environmental variability for greater restoration success.